Reducing employee turnover in hospitals: estimating the effects of hypothetical improvements in the psychosocial work environment - Mathisen, Jimmi; Nguyen, Tri-Long; Jensen, Johan Høy; Rugulies, Reiner; Rod, Naja Hulvej (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'Poor psychosocial work environments in hospitals are associated with higher employee turnover. In this prospective cohort study, we aimed to identify and quantify which aspects of the psychosocial work environment have the greatest impact on one-year employee turnover rates within a hospital setting, both overall and within occupational groups. ' ' METHODS ': 'The study population included 24 385 public hospital employees enrolled in the Danish Well-being in Hospital Employees cohort in 2014. We followed the participants for one year and registered if they permanently left their workplace. Using baseline sociodemographic, workplace, and psychosocial work environment characteristics, we applied the parametric g-formula to simulate hypothetical improvements in the psychosocial work environment and estimated turnover rate differences (RD) per 10 000 employees per year and 95% confidence intervals (95% CI). ' ' RESULTS ': 'Of the 24 385 participants, 2552 (10.5%) left the workplace during the one-year follow-up. Up to 44% of this turnover was potentially preventable through hypothetical improvements in the psychosocial work environment. The specific hypothetical improvements with the largest effects were in satisfaction with work prospects (RD -522 turnovers per 10 000 person-years, 95% CI -536– -508), general job satisfaction (RD -339, 95% CI -353– -325) and bullying (RD -200, 95% CI -214– -186). The potential for preventing turnover was larger for nurses than for physicians and other healthcare employees. ' ' CONCLUSIONS ': 'Improvements in the psychosocial work environment may have great potential for reducing turnover among hospital staff, particularly among nurses.
Keywords: employee exit; employee turnover; health services research; healthcare; hospital; hospital staff; occupational health; parametric g-formula; psychosocial; simulation study